The Influence of Brand Image on Willingness To Pay Premium Price Through Brand Love - Hibban , Ihfanny Achmad; Dian Wahyudi, Handri (Adpebi Science Series, 2022)
Indonesia is one of the markets for smartphone users which is quite large, one of the well-known smartphone brands circulating in the Indonesian market is Apple.Inc with its smartphone product, namely the iPhone. Smartphone-related innovations really have a lot of fans, especially in Generation Z. Enhancing a strong brand image creates a brand that excels in competition. This causes consumer behavior to be affected and then can lead to a sense of love for the brand, then consumers are willing to spend more money to buy iPhone products. This research uses a quantitative approach with descriptive and explanatory research types. The population and research sample are Generation Z who are customers of Apple brand smartphone products with iPhone product lines in the city of Malang (infinite population) with a total of 150 respondents. The analysis used is path analysis. The results showed that the description of Brand Image, Brand Love, and, Willingness to Pay Premium Price was very good, Brand Image had a positive and significant effect on Willingness to Pay Premium Price and Brand Love, while Brand Love had a significant effect on Willingness to Pay Premium Price. ; and Brand Image has a positive and significant indirect effect on Willingness to Pay Premium Price through Brand Love. Brand Love, and, Willingness to Pay Premium Price is very good, Brand Image has a positive and significant effect on Willingness to Pay Premium Price and Brand Love, while Brand Love has a significant effect on Willingness to Pay Premium Price; and Brand Image has a positive and significant indirect effect on Willingness to Pay Premium Price through Brand Love. Brand Love, and, Willingness to Pay Premium Price is very good, Brand Image has a positive and significant effect on Willingness to Pay Premium Price and Brand Love, while Brand Love has a significant effect on Willingness to Pay Premium Price; and Brand Image has a positive and significant indirect effect on Willingness to Pay Premium Price through Brand Love.